Quality of Life among People Survived from Terroristic Explosions: A Retrospective Cohort Study - DJassam, Mohammed; Abed Marzook, bAhmed; Abdul raheem, Yousif (AL-Kindy College Medical Journal, 2014)
Background: Increasing interest in quality of life (QoL) is the new approach for understanding and improvement of health care. Although there are many studies about quality of life, there is deficiency of data about quality of life of peoples survived from terroristic explosions.Objectives: To study the QoL for peoples survived from terroristic explosions and compare it with that of a controlled people. Methods: This study was conducted between, 1st of July till 31st of December 2013. The sample of this study was collected from peoples attending the outpatient clinics in four primary health care centers, Baghdad city (2 from Rusafa and 2 from Karkh). 183 individuals proved to be exposed to terroristic explosion and 199 individual not exposed to such event were recruited and Arabic version of the World Health Organization (WHO) self-reporting questionnaire (WHO-QoL-BRIEF) was used to assess the QoL.Results: This study revealed that peoples exposed to event of terroristic explosion show a serious defect in all domains of QoL (physical, psychological, social and environmental) as compared with that for non exposed peoples to such accidents in the same areas of the study.Conclusions: This study showed that peoples survived from terroristic explosions have a low QoL indicators as compared with those not exposed to such trauma .